Moral distress, autonomy and nurse-physician collaboration among ICU nurses in Italy - Albarran, John W.; Drigo, Elio; Giannakopoulou, Margarita; Kalafati, Maria; Tsiaousis, George Z.; Papathanassoglou, Elizabeth; Karanikola, Maria; Mpouzika, Meropi (My University, 2014)
Aim To explore the level of moral distress and potential associations between moral distress indices and (1) nurse–physician collaboration, (2) autonomy, (3) professional satisfaction, (4) intention to resign, and (5) workload among Italian intensive care unit nurses. Background Poor nurse–physician collaboration and low autonomy may limit intensive care unit nurses' ability to act on their moral decisions. Methods A cross-sectional correlational design with a sample of 566 Italian intensive care unit nurses. Results The intensity of moral distress was 57.9 ± 15.6 (mean, standard deviation) (scale range: 0–84) and the frequency of occurrence was 28.4 ± 12.3 (scale range: 0–84). The mean score of the severity of moral distress was 88.0 ± 44 (scale range: 0–336). The severity of moral distress was associated with (1) nurse–physician collaboration and dissatisfaction on care decisions (r = −0.215, P < 0.001); and (2) intention to resign (r = 0.244, P < 0.0001). The frequency of occurrence of moral distress was associated with the intention of nurses to resign (r = −0. 209, P < 0.0001). Conclusion Moral distress seems to be associated with the intention to resign, whereas poor nurse–physician collaboration appears to be a pivotal factor accounting for nurses' moral distress. Implications for nursing management Enhancement of nurse–physician collaboration and nurses' participation in end-of-life decisions seems to be a managerial task that could lead to the alleviation of nurses' moral distress and their retention in the profession.
Keywords: Decision-making; Ethics; Resign; Work satisfaction